The Effect Of Convenience, Advertising and Trust On The Benefits Of Using Digital Wallets (E-Wallets) On D’top UMKM In Sukabumi City - Riekal Fahmi; Ratnawati Prayogi; Venjte G. Rombot; Marisi Pakpahan; Irwan Tanamas (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study aims to analyze the influence of ease of use, advertising, and benefits of digital wallets (e-wallets) on Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Sukabumi. Digital wallets have become increasingly popular as a payment tool, particularly in the culinary industry. This research focuses on how these three factors affect the decision of MSME operators to use e-wallets in their business operations. The research method used is quantitative, with data collection techniques through questionnaires distributed to owners and managers of culinary MSMEs in Sukabumi. The data obtained were analyzed using multiple linear regression to determine the influence of each independent variable (ease of use, advertising, and benefits) on the dependent variable (e-wallet usage). The results show that all three independent variables have a significant positive influence on the use of digital wallets among culinary MSMEs in Sukabumi. Ease of use and benefits have a more dominant influence compared to advertising in driving the decision to use e-wallets. This study contributes to the development of digital wallet marketing strategies and provides insights for MSME operators to leverage digital payment technology to improve business efficiency and competitiveness.